Wittgenstein: a transição do atomismo lógico para o holismo semântico - Moreira, Jorge Henrique Lima (2009)
The present study examines the paradigmatic change of Wittgenstein’s philosophy. Such a change takes place when the philosopher realizes that his atomistic approach has unsolving problems. The dissolution point of that conception concerns the change regarding the notion of elementary proposition/state of things, that is to say, when Wittgenstein realizes that it is no more reasonable conceiving them as logical atoms. His paper Some remarks on logical forms presents this breaking point and leads him to reevaluate his philosophical conception. Firstly, he is based on a phenomenological conception of language, but afterwords he negates it. Then, this study focuses on that break regarding his phenomenological conception, when Wittgenstein comes to defend a hypothetical conception of language, such as the Physics.